2015
DOI: 10.1016/j.scr.2015.05.007
|View full text |Cite
|
Sign up to set email alerts
|

The Sirt1 activator SRT3025 expands hematopoietic stem and progenitor cells and improves hematopoiesis in Fanconi anemia mice

Abstract: Fanconi anemia is a genetic bone marrow failure syndrome. Current treatment options are suboptimal and do not prevent the eventual onset of aplastic anemia requiring bone marrow transplantation. We previously showed that resveratrol, an antioxidant and an activator of the protein deacetylase Sirt1, enhanced hematopoiesis in Fancd2 mutant mice and improved the impaired stem cell quiescence observed in this disease. Given that Sirt1 is important for the function of hematopoietic stem cells, we hypothesized that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 40 publications
0
12
0
Order By: Relevance
“…38 New therapeutic approaches that have the ability to treat or prevent bone marrow failure and cancer are thus clearly needed for FA. 8,9,20,37,42 Here we show that the widely used diabetes drug metformin improves hematopoiesis and delays tumor formation in Fancd2 2/2 mutant mice. Of note, metformin is the first compound to improve both of these FA phenotypes: oxymetholone, 9 resveratrol, 8 sirtuin activator, 20 and N-acetylcysteine 42 all improve hematopoiesis in Fancd2 2/2 mice, but none has been shown to diminish tumor incidence.…”
Section: Discussionmentioning
confidence: 64%
See 3 more Smart Citations
“…38 New therapeutic approaches that have the ability to treat or prevent bone marrow failure and cancer are thus clearly needed for FA. 8,9,20,37,42 Here we show that the widely used diabetes drug metformin improves hematopoiesis and delays tumor formation in Fancd2 2/2 mutant mice. Of note, metformin is the first compound to improve both of these FA phenotypes: oxymetholone, 9 resveratrol, 8 sirtuin activator, 20 and N-acetylcysteine 42 all improve hematopoiesis in Fancd2 2/2 mice, but none has been shown to diminish tumor incidence.…”
Section: Discussionmentioning
confidence: 64%
“…37 Our results indicate that metformin can ameliorate both of these key phenotypes of FA, and that its beneficial action was specific to FA mutant mice. In contrast, oxymetholone and the sirtuin activator SRT3025 affect both wild-type and mutant stem cells equally, 9,20 indicating that their mechanisms of action do not target the pathophysiology of FA bone marrow failure. Furthermore, it is particularly intriguing that the chronic administration of metformin significantly increases the frequency of HSCs in the adult Fancd2 2/2 mice.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Loss of the EGR1 gene with deletions of 7q31 or TP53 alone played a role in at least two signaling molecules of genipin-induced apoptosis in gastric cancer cells (88). Another article revealed that the down-regulation of EGR1-p21 expression provides a mechanism for improved hematopoiesis (89). Histone deacetylase (HDAC) inhibitors can reactivate EGR1 in various cell types, leading to decreased cell proliferation and increased cell apoptosis (90).…”
Section: Pathogenesis Mechanism Of Aml By Egr1mentioning
confidence: 99%